Influence Of the Simulation Program Methods to the Students Learning Outcomes on the Subject Of the Microcontroller System - Edidas (Journal of physics. Conference series, 2019)
This study aims to see the effect of program simulation methods on the learning outcomes of microcontroller systems. The microcontroller program simulation method is done in two ways, namely through hardware assembly and software assembly. Simulation through hardware devices using triner kits, while simulating through software use Proteus application software. This type of research is a quasi-experimental. The research design uses nonequivalent control group design techniques. The sample group is not randomly selected but is chosen based on the class that is already in the lecture. Learning outcomes variable (Y) while program simulation method (X). The research data analysis was carried out with Variance Analysis (ANOVA) to see the effect of the program simulation method on the learning outcomes of the microcontroller system.